(untitled) (The Planet, 2024)
Introduction: The widespread use of smartphones has led to increased health concerns, including conditions like de Quervain’s tenosynovitis, also known as texting thumb or gamer’s thumb. This condition affects the tendons on the thumb side of the wrist and is associated with the overuse of handheld devices for communication, entertainment, and information retrieval. Aim of the study: This study aimed to assess the relationship between the overuse of smartphones and de Quervain’s tenosynovitis. Methods and materials: This cross-sectional study was conducted at Department of Orthopedic Surgery, United Hospital Limited Gulshan, Dhaka, Bangladesh from January, 2021 to December, 2023. The study included 220 young adults identified as excessive smartphone users through convenient sampling. An online questionnaire assessed smartphone usage behaviors and their association with de Quervain’s tenosynovitis (DQT). The Finkelstein test diagnosed DQT, and data analysis utilized SPSS version 23.0. Results: In comparing the ages, duration of smartphone use, and smartphone screen sizes, we found significant correlations between de Quervain’s tenosynovitis cases and non-de Quervain’s tenosynovitis cases where the P values were 0.006, 0.032, 0.009 respectively. On the other hand, in comparing the causes of using smartphones, we did not find any correlation (P>0.05). Conclusion: Extended daily use of smartphones within a certain age range, particularly with smaller screens, may pose potential risks for de Quervain’s tenosynovitis in young adults.